Comparison of Neutrophil Gelatinase Associated Lipocalin with Serum Creatinine for Early Detection of Decrease in Estimated Glomerular Filtration Rate - Fawaad Sana; Syed Raza Jaffar; Dilshad Ahmed Khan; Najam uddin; Mohammad Anwar Magsi; Muhammad Tahir Khadim; Irfan Ali Mirza; Farhan Akhtar (Journal of Bahria University Medical and Dental College)
Objective: To determine the accuracy of Neutrophil Gelatinase Associated Lipocalin (NGAL) at 2 h compared to serum creatinine at 48 h after Computerized Tomography (CT) scan with contrast medium for early detection of decrease in estimated Glomerular Filtration Rate (eGFR).